Lifestyle Changes in the Anak Dalam Tribe Community in Tanah Tinggi Subdistrict, Bungo Regency, Jambi Province - Yulinda, Meli; Suharti; Yurisman (Kirana Publisher (KNPub), 2024)
The aim of this research is to describe the reasons behind lifestyle changes in the Anak Dalam Tribe community in Tanah Grow District, Bungo Regency, Jambi Province. Describe the forms of lifestyle change in the Anak Dalam Tribe community in Tanah Grow District, Bungo Regency, Jambi Province. The research method used is qualitative research. Data was collected through field observations, interviews and documentation. The theory used is the Theory of Social Change according to JL Gillin and JP Gillin (in Soekanto and Budi Sulistyowati, 2015: 261) and the Lifestyle Theory according to Wibowo and Riyadi (in Minarti, 2020: 12). The results of this research show that the background to lifestyle changes in the Anak Dalam Tribe community consists of external factors, namely the natural environment, government and reference groups, as well as internal factors, namely mindset, self-awareness and religion. The form of lifestyle change in the Anak Dalam Tribe community includes four aspects such as clothing, changing clothing from traditional to modern clothing. Residence, change of residence from the forest to a special house. Religion, change of belief from animism to Islam. Education, changes in education from those who did not know formal education to now they have had formal education and know writing.